Asperger Syndrome and Assistive Technologies - Hasioti , Theopisti Marina; Drigas, Athanasios; Loukeris , Dionysis; Gavriilidou , Zoe (Technium Social Sciences Journal, 2022)
In this paper we present a study which revolves around the importance of ICTs (Information and communication technologies) at people with Asperger Syndrome. The goal of the study was to unveil how people with autism such as Asperger Syndrome could use ICTs in order to enhance and facilitate their teaching, learning and everyday lifestyle. ICTs will be potentially a tool towards overcoming difficulties of these individuals.